Implementasi Hybrid Learning Berbasis Diferensiasi dalam Mendukung Kurikulum Merdeka di Sekolah Dasar - Shalsya Nazyfha; Ananta Lestari Br Sembiring; Berta Arista Br Damanik; Mutiara Uli Arta Tambunan; Liza Aulia Yusuf; Asna Istikmalatul Muktamaroh (Jurnal Keluarga Sehat Sejahtera, 2026)
Educational changes in the Society 5.0 time require new and creative ways to teach that keep up with technology and what students need. This research looks into how the Independent Curriculum is being used with hybrid learning in elementary schools, focusing on personalizing education for different students. The study is done using a qualitative method that describes what happens by reviewing literature and analyzing teaching methods. The findings show that using hybrid learning allows for a flexible way of learning by mixing online and in-person activities, which helps to meet various student learning styles, interests, and abilities. In addition, the approach of personalizing the Independent Curriculum lets teachers change their teaching methods, content, and assessments to better fit each student's needs. Therefore, this change not only enhances the quality of learning but also boosts important skills for the 21st century like critical thinking, creativity, teamwork, and being good with technology. In conclusion, this study finds that using a hybrid learning approach that is based on personalization is a smart and effective way to help carry out the Independent Curriculum during the Society 5.0 period in elementary education.